The Effect of Chromium Picolinate Supplementation on the Pancreas and Macroangiopathy in Type II Diabetes Mellitus Rats - Shan Huang; Wenfang Peng; Xiaohong Jiang; Kan Shao; Lili Xia; Yubin Tang; Jiayin Qiu (Journal of Diabetes Research)
Purpose. The aim was to explore the effect of the chromium picolinate (CrPic) administration on the pancreas and macroangiopathy of type II diabetes mellitus rats. Methods. The type II diabetes mellitus (T2DM) rat model was induced by low-dose streptozotocin (STZ). The rats were randomly divided into 5 groups (ten rats in each group). After supplementing CrPic for 15 weeks, the histopathological examination was performed by hematoxylin-eosin (HE) staining. Serum insulin and NO level were determined by radioimmunoassay and colorimetry, respectively. Serum glycosylated hemoglobin (HbA1C), adiponectin (APN), advanced glycation end products (AGES), and apelin were measured by ELISA. Real-time reverse transcription polymerase chain reaction (RT-PCR) was applied for detecting the mRNA expression of APN and apelin. Results. After CrPic treatment, compared with the T2DM control group (group 2), pancreas sections stained with HE showed the completed pancreatic cells structure and no inflammatory infiltration in groups 4 and 5. In addition, the levels of serum NO and insulin were significantly increased and the serum levels of HbA1C, AGES, APN, and apelin were significantly decreased in groups 4 and 5 compared with group 2. The mRNA expression of APN and apelin in groups 4 and 5 was also recovered to the normal level. Conclusion. CrPic can recover the function of Β-cells and alleviate macroangiopathy in STZ-induced T2DM rats.